2022
DOI: 10.7554/elife.73252
|View full text |Cite
|
Sign up to set email alerts
|

α-/γ-Taxilin are required for centriolar subdistal appendage assembly and microtubule organization

Abstract: The centrosome composed of a pair of centrioles (mother and daughter) and pericentriolar material, and is mainly responsible for microtubule nucleation and anchorage in animal cells. The subdistal appendage (SDA) is a centriolar structure located at the mother centriole’s subdistal region, and it functions in microtubule anchorage. However, the molecular composition and detailed structure of the SDA remain largely unknown. Here, we identified α-taxilin and γ-taxilin as new SDA components that form a complex vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…We speculate that taxilin family proteins have a similar ability to engage diverse sets of proteins through their CCD and IDPRs. While Txlnb is selectively expressed in striated muscle and has an unclear biological function, Txlna and Txlng are ubiquitously expressed across tissues, associate with centrosome and pericentriolar proteins 11,12 , bind to microtubules 54 , regulate protein trafficking 55 and influence the accumulation of UPS-targeted substrates 27 . Our results show that Txlnb increases UPS efficiency, though it remains unclear exactly how this occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that taxilin family proteins have a similar ability to engage diverse sets of proteins through their CCD and IDPRs. While Txlnb is selectively expressed in striated muscle and has an unclear biological function, Txlna and Txlng are ubiquitously expressed across tissues, associate with centrosome and pericentriolar proteins 11,12 , bind to microtubules 54 , regulate protein trafficking 55 and influence the accumulation of UPS-targeted substrates 27 . Our results show that Txlnb increases UPS efficiency, though it remains unclear exactly how this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…We stumbled upon the taxilin gene/protein family (Txlna, Txlnb, and Txlng) 10 that encodes centrosomal adapter proteins. 11,12 One member, Txlnb, is highly enriched in cardiomyocytes, but its roles in cardiac biology and disease remain understudied [13][14][15] . Notably, we found that Txlnb influences protein homeostasis in cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Significant increases were also observed in proteins linked to cytoskeletal integrity and architecture. Striatin-interacting protein 2 (STRIP2) (0.58-log2FC; 1.49-FC) is involved in regulating cell morphology and cytoskeletal organization [46], protein 4.1 (EPB41) (0.23-log2FC; 1.18-FC) regulating spectrin-actin interaction contributing to cellular mechanical stability [47], and alpha-taxilin (TXLNA) (0.28-log2FC; 1.22-FC), involved in microtubule organization [48].…”
Section: Proteomic Analysis Of the Ecm Enriched Fraction Reveals The ...mentioning
confidence: 99%
“…Moreover γ-TXLN ablation may induce tau hyperphosphorylation in AD patients [ 131 ]. In the past few years, even if large body of evidence [ 132 , 133 ] supported physiological relevance of the taxilin family, further research on the role of family member γ-TXLN in neuropathology would be of great value.…”
Section: Human Nlrp2 Connectome With String Databasementioning
confidence: 99%